Evaluating the fit and performance of flat-fold, cup, and three-panel respirators among Thai healthcare personnel - Wangsan, Kampanat; Sapbamrer, Ratana; Sirikul, Wachiranun; Kiratipaisarl, Wuttipat; Ongprasert, Krongporn; Assavanopakun, Pheerasak; Surawattanasakul, Vithawat; Kitro, Amornphat; Panumasvivat, Jinjuta; Wongcharoen, Amnart (Frontiers in Public Health, 2025)
IntroductionHealthcare personnel (HCP) face high risks of airborne infections, including coronavirus disease 2019 (COVID-19), tuberculosis, and measles. Filtering facepiece respirators (FFRs) are critical for protection but require an adequate fit for effectiveness. Limited studies have explored the fit performance of different FFR designs in Southeast Asian populations. This study evaluates fit factors and pass rates of flat-fold, cup-shaped, and three-panel flat-fold respirators among Thai HCP and examines the influence of facial anthropometry on fit outcomes.MethodsA cross-sectional study was conducted with 223 HCP at a university hospital in Chiang Mai, Thailand. Quantitative fit testing of three NIOSH-certified N95 respirators—flat-fold, cup-shaped, and three-panel flat-fold—was performed using a TSI Portacount Pro+ 8,038 device. The Occupational Safety and Health Administration (OSHA) Condensation Nuclei Counter protocol, comprising bending, talking, and head movement exercises, was followed. Fit factors, calculated as the harmonic mean, required a passing threshold of ≥100. Twenty-two facial anthropometric dimensions were also measured. Statistical analyses included the Kruskal–Wallis test, Fisher’s exact test, and logistic regression.ResultsPass rates were 5.4% for flat-fold respirators (median fit factor [FF]: 25), 51.1% for cup-shaped models (median FF: 104), and 82.5% for three-panel flat-fold designs (median FF: 191), with significant differences (p < 0.001). The three-panel flat-fold maintained FF values near 200 across exercises. Anthropometric predictors varied by FFR type: head length (Adj. OR: 1.16) and nose length (Adj. OR: 1.28) influenced flat-fold models, while nasal bridge breadth (Adj. OR: 1.11) affected cup-shaped models.ConclusionThe three-panel flat-fold respirator exhibited superior adaptability, highlighting its potential as the preferred choice for Thai HCP. The low pass rate of flat-fold designs underscores the need for region-specific respirator designs. Findings emphasize the importance of localized fit testing and the development of regional fit test panels to enhance protection. Further research is needed to explore fit retention, comfort, and usability in real-world conditions.